First record of Diastatidae (Diptera: Ephydroidea) from Brazil, with the description of a new species - Costa, Sávio Cunha; Pirani, Gabriela; Mathis, Wayne N. (Zootaxa, 2023)
The ephydroid family Diastatidae is recorded for the first time from Brazil. A new species, Diastata fachini Costa, Pirani & Mathis, sp. nov. which was collected from the Atlantic Forest, is described. The description is based on an adult male and female and includes photographs and detailed illustrations.